2017
DOI: 10.1063/1.4981860
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of warpage on plastic injection moulding part with MGSS conformal cooling channels moulds using response surface methodology (RSM)

Abstract: Abstract.Nowadays, there are various methods of optimisation works that have been explored by many researchers to find the appropriate processing parameters setting of injection moulding process. From the previous researches, it was reported that the optimisation work improved the moulded part quality. Apart from quality, the productivity in the injection moulding process also plays an important role. Therefore, some of the researchers have introduced the conformal cooling channels which have been proven to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Their findings showed that RSM sufficed in warpage optimization of both SCC and CCC. Full factorial DoE was used to optimize the warpage resulting from a milled groove CCC with a square CS [17]. They found out that warpage was affected by the cooling time more than the temperature of the molten plastic and packing pressure.…”
Section: Sensitivity-based Design Attempts To Understand the Relation...mentioning
confidence: 99%
“…Their findings showed that RSM sufficed in warpage optimization of both SCC and CCC. Full factorial DoE was used to optimize the warpage resulting from a milled groove CCC with a square CS [17]. They found out that warpage was affected by the cooling time more than the temperature of the molten plastic and packing pressure.…”
Section: Sensitivity-based Design Attempts To Understand the Relation...mentioning
confidence: 99%
“…ese include the injection speed, injection pressure, cooling time, packing pressure, mold temperature, packing time, and melt temperature. e injection speed and injection pressure have been identified in [30,31], whereas the cooling time, packing pressure, mold temperature, packing time, and melt temperature have been identified in [3,[31][32][33][34][35][36] as having an effect on the product quality. e experiments in this work were conducted on an injection molding unit known as the Arburg Allrounder 420 C [37], and a simple mold with product dimensions depicted in Figure 2 was used.…”
Section: Injection Molding Experimentsmentioning
confidence: 99%
“…Lowered cycle time translates to an increase in production rate. Previous research shows that reduction in cycle time can lead to a pro t income [13,14]. This makes the application of CCC very attractive, and it has been made possible by the application of 3D manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Their ndings showed that RSM su ced in warpage optimization of both SCC and CCC. Full factorial DoE was used to optimize the warpage resulting from a milled groove CCC with a square CS (Hazwan, Shayfull, Sharif, Zainal, et al, 2017). They found out that warpage was affected by the cooling time more than the temperature of the molten plastic and packing pressure.…”
Section: Introductionmentioning
confidence: 99%